Detección y aislamiento del Parvovirus porcino en Medellín, Colombia (2003)
ABSTRACT: The objective of this study was to detect the viral antigen and isolate the porcine parvovirus (PVP). Supernatants of lung tissue of 75 dead porcine foetuses from selected farms in Colombia were studied by Haemagglutination assay (HA) and viral propagation in PK15 cell culture (Porcine Kidney). The foetuses had a crown rump length between 8 to 25cm. 73.3% (55/75) of the foetuses were positive to HA and the 93.54% (52/55) of the positive cases were 45 to 65 days old while the 6.46% (3/55) were 66 to 75 days old. The 26.7%(20/75) of the cases were negative to HA. The 90% (18/20) of the negative cases, were 66 to 95 days old. The virus was isolated from two mummies positives to HA, 3.6%(2/55 ), which were 48 and 51 days old, respectively. It was characterized like PVP by its HA activity, cytopathic effect in PK15 cell culture, and it was resistant to 20% ether and stable at p H 3.0. The conclusion was that a high percentage of analysed foetuses were infected with PVP, and the detection of virus antigen by HA, presents higher titles in foetuses younger than 65 days (17 cm length).